Microstructure-corrosion behaviour relationship of micro-alloyed Mg-0.5Zn alloy with the addition of Ca, Sr, Ag, In and Cu. (October 2020) - Jin, Yiming; Blawert, Carsten; Yang, Hong; Wiese, Björn; Feyerabend, Frank; Bohlen, Jan; Mei, Di; Deng, Min; Campos, Maria Silva; Scharnagl, Nico; Strecker, Katharina; Bode, Julia; et al.
Abstract: The effects of micro-addition (0.2 wt.%) of Ca, Sr, Ag, In and Cu on the microstructure and corrosion properties of the as-cast Mg-0.5Zn alloy were systematically studied. It is found that the grain refinement efficiency and intermetallics forming ability differed greatly among these elements. Si impurity also played a vital role in the precipitates formation in all systems. It is generally observed that Mg-Zn-Ca possessed the highest corrosion resistance due to the refined grain size, limited intermetallics and uniform corrosion, whereas Mg-Zn-Cu showed the highest corrosion rate due to the coarse grains, intermetallics activity and severe pitting corrosion. With the exception of Mg-Zn-Cu, the corrosion performances of Mg-0.5Zn(-0.2X) alloys were comparable with the higher concentrated systems from literature, indicating the feasibility of these micro-alloying systems for biomedical applications. Graphical Abstract: Unlabelled Image Highlights: The microstructures and corrosion properties of micro-alloyed Mg-0.5Zn(-0.2X) systems (X: Ca, Sr, Ag, In, Cu) are systematically studied. Mg-Zn-Ca has the lowest corrosion rate while Mg-Zn-Cu has the highest corrosion rate in 0.9% NaCl solution. The corrosion performances of Mg-0.5Zn(−0.2X) alloys are comparable with those of the highly-alloyed systems from literature Si is influential in intermetallics formation and thus should be limited to avoid relevant phase formation.